Hybrid planar optofluidic integration - HAWKINS AARON ROE; SCHMIDT HOLGER (2017)
The invention relates to hybrid planar optofluidic integration. The invention provides an optofluidic device and a manufacturing method thereof. The optofluidic device is used for analyzing a sample and comprises optical layers of a plurality of waveguides and a plurality of fluidic layers. The fluidic layer in the plurality of fluidic layers is attached to the optical layers. The optofluidic device can introduce a liquid solution into an optofluidic platform and perform optical detection on single particles contained in the liquid solution with extremely high sensitivity without the need of advanced microscopy equipment. 本发明涉及混合型平面光流控集成。本发明提供种光流控装置及其制造方法。所述光流控装置用于分析样品，包括：包括多个波导的光学层；以及多个流控层，其中所述多个流控层中的流控层附接到所述光学层。所述光流控装置可以将液体溶液引入光流控平台中并且可以对液体溶液中的单粒子进行具有极高灵敏度的光学检测而不需要先进的显微镜设备。